2018
DOI: 10.1039/c8cp03645d
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nanoparticles on the polarizabilities and hyperpolarizabilities of photochromic molecules

Abstract: We consider how nanoparticles affect molecular photoswitches and our focus is on how the polarizabilities and hyperpolarizabilities of the dihydroazulene/vinylheptafulvene system changes, when the compounds interact with gold nanoparticles. We have utilized a combined quantum mechanical/molecular mechanical approach, where the photochromic molecule is described by time-dependent density functional theory using the long-range-corrected CAM-B3LYP functional and the correlation consistent aug-cc-pVDZ basis-set. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…2) The other two distances are, respectively, 1.0 Å and 2.0 Å longer than the shortest distance. Previous investigations showed that the gold NP only has a minimal effect on the molecules for distances greater than 5 Å [40].…”
Section: Achmentioning
confidence: 98%
See 1 more Smart Citation
“…2) The other two distances are, respectively, 1.0 Å and 2.0 Å longer than the shortest distance. Previous investigations showed that the gold NP only has a minimal effect on the molecules for distances greater than 5 Å [40].…”
Section: Achmentioning
confidence: 98%
“…The main purpose of this investigation is to study how the absorption spectra change for DHA, s-cis-VHF and s-trans-VHF as the molecules interact with the gold NP [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The MM part of the system is the silver and copper nanoparticles that are modeled as hemispheres consisting of 70 atoms. This specific size of the nanoparticles is chosen to allow for a comparison to earlier work , with hemispherical gold nanoparticles of 70 atoms. The choice of coordination surface is an fcc(111) surface as this has formerly been shown to be a likely site of coordination for the molecules. , Furthermore, we consider only one cluster geometry and size as earlier studies ,, showed changes of less than 5% in the desired molecular property when changing the size and geometry of the nanoparticles.…”
Section: Computational Approachmentioning
confidence: 99%
“…18 Furthermore, we found that the NPs can enhance both one and two photon absorption of these systems while also providing significant redshifts in the absorption and clear alterations in the electric properties. [19][20][21] Hence, the coupling of such NPs to the NBD/QC system could be used as catalyst for the thermal back reaction while also possible tuning optical properties for solar energy storage.…”
Section: Introductionmentioning
confidence: 99%